Awareness and self-care practice regarding prevention of chronic kidney disease among hypertensive patients at the University Teaching Hospital of Butare, Rwanda - Pierre Marie Theos Mbabazi; Geldine Chironda; Emmanuel Bimenyimana Gapira; Shyaka Jean Claude; Didace Ndahayo; Lakshmi Rajeswaran (Elsevier, 2022)
Introduction: There is a strong relationship between Hypertension and Chronic Kidney Disease. To minimize and prevent the occurrence of Chronic Kidney Disease, hypertensive patients have to be aware of their condition and adhere to recommended self-care practice. Aim of the study: To assess the awareness and self-care practice regarding the prevention of Chronic Kidney Disease among patients living with hypertension at the University Teaching Hospital of Butare. Methodology: The study design was descriptive cross-sectional. A sample size of 140 was selected using purposive sampling strategy. Data was collected using a closed-ended questionnaire. Descriptive and inferential statistics were used to analyze data. Results: Nearly 49% had a low level of awareness, and moderate self-care practice was observed in 56.5% of study participants. Educational level was discovered to be associated with the awareness (p = .026). Factors associated with self-care practice were age (p = .000), marital status (p = .003), educational level (p.020), occupation (p = .021) and residence (p = .026). A significant weak positive relationship between awareness and self-care practice of participants (r = 0.254, p = 0.02) was established. Conclusion: Altered levels of awareness and self-care practice regarding Chronic Kidney Disease prevention was revealed. Health care professionals including nurses need to intensify health education to improve awareness and provide adequate information to hypertensive patients on the importance of good self-management. Further research is called for to identify further factors contributing to moderate self-care practice of preventing CKD since awareness only explained 6.4% variance.